Sevoflurane promotes the apoptosis of laryngeal squamous cell carcinoma in-vitro and inhibits its malignant progression via miR-26a/FOXO1 axis. Issue 1 (1st January 2021) - Liu, Dan; Wan, Lang; Gong, Hao; Chen, Shiming; Kong, Yonggang; Xiao, Bokui
ABSTRACT: Laryngeal squamous cell carcinoma (LSCC) is a laryngeal malignancy with a high mortality rates, and its treatment remains difficult. Sevoflurane is a surgical anesthesia which has anti-tumor effect. This investigation assessed the effects of LSCC cells treatment with Sevoflurane in vitro and in vivo. Hep-2 and Tu177 cells, human LSCC samples and BALB/C nude mice were used for result assessments. Cell viability, proliferation, migration and invasion were assessed via Cell Count Kit-8, wound healing assay and transwell invasion assay respectively. MiR-26a and FOXO1 expressions was examined by qRT-PCR. FOXO1, E-cadherin, N-cadherin and vimentin activities were examined by Western blotting. Moreover, animal experiments were performed to verify our findings in vitro . Lastly, miR-26a and FOXO1 expression levels in clinical samples were analyzed. According to the results, Sevoflurane decreased LSCC cells' viability and even stimulated their apoptosis in vitro and in vivo . Moreover, it could reduce the migration, invasion and EMT. Mechanistically, sevoflurane could downregulate miR-26a expression and that miR-26a could negatively modulate FOXO1 activity. Thus, sevoflurane could increase FOXO1 activity. In the clinical samples, miR-26a expression was significantly upregulated, but FOXO1 was remarkably down-regulated and miR-26a expression in LSCC was linked with better prognosis. In conclusion, MiR-26a is increased and FOXO1 is reduced in human LSCC, Sevoflurane inhibits proliferation and mediates apoptosis of LSCC cells. Further, MiR-26a binds FOXO1 directly, and FOXO1 expression is down-regulated by Sevoflurane. Finally, Sevoflurane triggers LSCC cells apoptosis in vivo. Sevoflurane use to target miR-26a/FOXO1 may be a novel alternative for LSCC therapy.